The Demand for Monetary Assets in the UK; a Locally Flexible Demand System Analysis - Thomas Elger (Lund University, School of Economics and Management, Department of Economics, 2002)
This study provides strong empirical support for modeling the demand for monetary assets within a consumer demand framework. We estimate a linearised locally flexible almost ideal demand system, containing five monetary assets, over the period 1991Q4 to 1998Q4. Estimating the system in differences is a convenient method to account for possible non-stationarity in the data, a major concern for applied macroeconomists. All significant un-compensated own-price elasticities are negative. The compensated own-price elasticities are insignificant and the majority of the income elasticities are significant. Theoretical homogeneity and symmetry propositions are satisfied.
Keywords: C43; D12; E41; 330; Money Demand; Almost Ideal Demand System